2019
DOI: 10.1177/1203475419847956
|View full text |Cite
|
Sign up to set email alerts
|

The Real-Life Effectiveness and Safety of Omalizumab Updosing in Patients With Chronic Spontaneous Urticaria

Abstract: Background: Omalizumab is a third-line treatment for chronic spontaneous urticaria (CSU). Studies investigating the use of higher doses of omalizumab in patients unresponsive to regular doses are limited. Objectives: This study aims to investigate the effectiveness and safety of omalizumab 450 mg in CSU. Methods: A retrospective cohort study was conducted. The response to therapy was evaluated using the Urticaria Activity Score over 7 days (UAS7) and the Urticaria Control Test (UCT). Patients showing complete … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 32 publications
(52 reference statements)
1
8
0
Order By: Relevance
“…In our study, we found that urticaria patients who received greater than the standard dose of omalizumab had significantly lower baseline IgE levels (Table 4) than those who received the standard doses of the medication (p=0.003). These findings are in agreement with previously published data; therefore, baseline IgE levels may identify patients who do not respond to the standard dose of omalizumab and act as a predictor of patients with severe skin lesions [24]. In our cohort of patients on omalizumab, we observed minimal adverse effects, which included 2 cases of pruritus, 1 case of urticaria, and 1 case of vasovagal reaction.…”
Section: Discussionsupporting
confidence: 92%
“…In our study, we found that urticaria patients who received greater than the standard dose of omalizumab had significantly lower baseline IgE levels (Table 4) than those who received the standard doses of the medication (p=0.003). These findings are in agreement with previously published data; therefore, baseline IgE levels may identify patients who do not respond to the standard dose of omalizumab and act as a predictor of patients with severe skin lesions [24]. In our cohort of patients on omalizumab, we observed minimal adverse effects, which included 2 cases of pruritus, 1 case of urticaria, and 1 case of vasovagal reaction.…”
Section: Discussionsupporting
confidence: 92%
“…Also, patients previously treated with cyclosporin A and older patients (> 57 years of age) who may be non-responders to the standard dose can be expected to have greater success with updosing omalizumab [ 52 ]. Patients with lower IgE levels are more likely to be non-responders to omalizumab and therefore required updosing more often than the patients without [ 53 ]. Overall, it was observed that updosing in suboptimal responders was safe and effective.…”
Section: Discussionmentioning
confidence: 99%
“…Salman et al [53] reported the effectiveness and safety of omalizumab 450 mg in a retrospective cohort study of 72 patients treated with omalizumab 300 mg and 450 mg. Of 13 patients with CSU who were unresponsive to omalizumab 300 mg and updosed to 450 mg, six had complete response and three had good disease control with a mean UAS7 that decreased from 18.6 to 5.1 and a mean UCT score that increased from 8.6 to 12.0. A partial response to omalizumab updosing was noted in 2 patients, while 2 patients were non-responders.…”
Section: Real-world Evidence Of Omalizumab Treatment and Updosing In Csumentioning
confidence: 99%
“…Alternative strategies in those patients include updosing omalizumab, switching to immunosuppressive treatment, for example, cyclosporine or combining omalizumab with other systemic treatments. The studies have shown that updosing to 450 or 600 mg provides better disease control in 32-75% of patients [55][56][57][58][59][60]. The need for updosing was associated with older age (> 57 years old), higher baseline body mass index (BMI), lower baseline urticaria control test (UCT) scores, lower baseline IgE levels, and immediate use of CsA [55,57,58].…”
Section: Omalızumab: From Development To Current Challengesmentioning
confidence: 99%
“…The studies have shown that updosing to 450 or 600 mg provides better disease control in 32-75% of patients [55][56][57][58][59][60]. The need for updosing was associated with older age (> 57 years old), higher baseline body mass index (BMI), lower baseline urticaria control test (UCT) scores, lower baseline IgE levels, and immediate use of CsA [55,57,58]. The major shortcoming of immunosuppressive treatments is AEs, and the combined use of omalizumab with other systemic agents (e.g., cyclosporine, dapsone, colchicine) is based on anecdotal reports [61][62][63].…”
Section: Omalızumab: From Development To Current Challengesmentioning
confidence: 99%